87 PREDICTIVE VALIDITY OF SCREENING TOOLS USED BY A FRAILTY INTERVENTION TEAM IN AN IRISH EMERGENCY DEPARTMENT: A RETROSPECTIVE COHORT STUDY. (18th November 2021) - O'Carroll, S; Cremin, M; Meehan, E; O'Leary, H; Galvin, R; Fitzgerald, L; O'Connell, P; Mukherjee, P
Abstract: Background: Various screening tools exist to identify frail and at-risk older adults in the emergency department (ED). This can facilitate targeted assessment and management, leading to improve outcomes. This study evaluated the predictive validity of four screening tools used by an ED-based team of allied health professionals. Methods: The Variable Indicative of Placement (VIP) tool, Think Frailty Tool, Clinical Frailty Scale (CFS) and 4AT were administered to adults aged ≥75 years as part of assessment by the Frailty Intervention Therapy Team in an Irish ED. Outcomes were hospital admission; re-attendance within 28 or 90 days; and death within 28 or 365 days. Scores were dichotomised, and for each outcome, relative risks and sensitivity, specificity, positive and negative predictive values were calculated. Results: Over the six-month period, 429 individuals (median age:82 years) were assessed. Of these, 59% were VIP-positive, 81% screened at-risk of frailty on the Think Frailty Tool, 56% screened positive for frailty on the CFS, and 16% screened positive on the 4AT. Hospital admission, re-attendance at 28 and 90 days, and death within 28 and 365 days were 56%, 12%, 27%, 5%, and 23%, respectively. Positive screens on the VIP, Think Frailty Tool, CFS and 4AT were associated with significantly increased risk of hospital admission and death within 28 or 365 days ( p  < 0.05). Positive screens on the Think Frailty Tool and CFS were also associated with increased risk of 90-day re-attendance ( p  < 0.05). Of the four tools, the Think Frailty Tool had the highest sensitivity (86%–100%) for all outcomes. The CFS showed high sensitivity for detecting death within 28 or 365 days (95% and 84%, respectively), but lower sensitivity (68%–75%) for other outcomes. The 4AT demonstrated the lowest sensitivity for all outcomes (20%–46%). Conclusion: The Think Frailty Tool and CFS were the most useful for predicting adverse outcomes in this group.